Implementasi Penyusunan Paket Wisata dengan Kemampuan Interpretasi “Story Telling” pada Destinasi Super Prioritas Likupang, Minahasa Utara - Darmayasa; Muhammad Arifin; Margaretha Wadid Rante; Masri Ridwan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Implementation of Tourism Package Arrangement with “Story Telling” Interpretation Capability at Likupang Super Priority Destinations, North Minahasa. This activity aims to improve the skills of tour guide business actors in the super-priority destinations of Likupang, North Minahasa. The problems in Likupang include the lack of excellent service for tour guides. This has an impact on the interest of tourists visiting. The Bimtek process consists of 2 (two) stages, the knowledge transfer stage through theoretical classes and the demonstration stage through practice at tourist objects. Bimtek materials include Excellent Service, Tour Packages and